Ketogenic diet enhances the anti-cancer effects of PD-L1 blockade in renal cell carcinoma - Richard, Jeremy; Beauvillain, Céline; Benoit, Maxime; Barth, Magalie; Aubert, Cécile; Rolley, Cyrielle; Bellal, Sarah; Bourreau, Jennifer; Ferragu, Matthieu; Lebdai, Souhil; Chevrollier, Arnaud; Henrion, Daniel; et al. (Frontiers in Endocrinology, 2024)
Introduction: Clear cell renal cell carcinoma (ccRCC) is characterized by a predominant metabolic reprogramming triggering energy production by anaerobic glycolysis at the expense of oxydative phosphorylation. Ketogenic diet (KD), which consists of high fat and low carbohydrate intake, could bring required energy substrates to healthy cells while depriving tumor cells of glucose. Our objective was to evaluate the effect of KD on renal cancer cell tumor metabolism and growth proliferation. Methods: Growth cell proliferation and mitochondrial metabolism of ACHN and RENCA renal carcinoma cells were evaluated under ketone bodies (KB) exposure. In vivo studies were performed with mice (nude or Balb/c) receiving a xenograft of ACHN cells or RENCA cells, respectively, and were then split into 2 feeding groups, fed either with standard diet or a 2:1 KD ad libitum. To test the effect of KD associated to immunotherapy, Balb/c mice were treated with anti-PDL1 mAb. Tumor growth was monitored. Results: In vitro, KB exposure was associated with a significant reduction of ACHN and RENCA cell proliferation and viability, while increasing mitochondrial metabolism. In mice, KD was associated with tumor growth reduction and PDL-1 gene expression up-regulation. In Balb/c mice adjuvant KD was associated to a better response to anti-PDL-1 mAb treatment. Conclusions. KB reduced the renal tumor cell growth proliferation and improved mitochondrial respiration and biogenesis. KD also slowed down tumor growth of ACHN and RENCA in vivo. We observed that PDL-1 was significantly overexpressed in tumor in mice under KD. Response to anti-PDL-1 mAb was improved in mice under KD. Further studies are needed to confirm the therapeutic benefit of adjuvant KD combined with immunotherapy in patients with kidney cancer.